Prevalence of maxillary sinus jaw mucuous cysts in University Dental Radiology Service - Saraiva Neto, Joaquim Lira (2017)
Background: Mucosal cyst of the maxillary sinus or antral pseudo - cyst is one of great importance injury, being the pathology that affects more the maxillary sinus. Their discovery, in most cases, it is for the interpretation of the images in routine panoramic radiography. Aims: The research aimed to evaluate the prevalence of mucous cyst in maxillary sinus in radiology clinic at Ceara Federal University. Material and Methods: To this study conduction, were analyzed 1996 panoramic radiographs from a digital file obtained between April 2011 to April 2013. Results: Aspects as gender, affected side and teeth absence next to the cyst in the respective quadrant were evaluated.It was observed in the sample the occurrence of 45 patients with suggested images of mucous cysts in maxillary sinus,making a prevalence of 2.25%. From them, 26 (57.8%) were female and 19 (42.2%) were male. 48 maxillary sinuswere affected with the wound, from which28 (58.3%) it was in the left side and 20 (41.7%) in the right site. Three patients presented the wound in both sides, what represents 6.7% of the affected patients. From those 48 Mucous retention cyst, 40 (83.3%) were not related to an edentulous area in ipsilateral quadrant and 8 (16.7%) were shown next to an edentulous area. Conclusion: The conclusion was that the cyst of retention mucous in the maxillary sinus had prevalence in males and in the left side of the maxillary sinus. It was not found a relation between the cyst and the edentulous area.